The Effects of Health Education Using Traditional Herbs of Students Health Care, Ban Kok Chang School, Phangnga Province - Nantachai, Kanyapak; Thongjun, Chudabhorn; Prasomkit, Wilawan (Journal of Human and Society, Sisaket Rajabhat University, 2024)
This research is the quasi-experimental research. The one group had pretest-posttest before and after experiment and had the objectives to 1) to compare the knowledge scores on using traditional herbs for health care before and after receiving the health education od students, Ban Kho Chang school, Phangnga province, and 2) to study the satisfaction level of health education providing by using traditional herbs to health care for students, Ban Kok Chang School, Phangnga province. The sample group of this research was students who were studying in Prathomsuksa 4 to Matthayomsuksa 3 at Ban Kho Chang school, Phangnga province, in number of 43 students. By using the purposive sampling. The research tools were including a health education project, knowledge test, and satisfaction assessment form. The statistics that used for analyzing data were frequency, percentage, means, standard deviation, and hypothesis test with paired t-test. The results of the research found out that the sample group had a knowledge score on using traditional herbs for health care after receiving health education higher than before receiving health education at a significance level of 0.01 and the overall satisfaction level of the sample group was in high level of health education using traditional herbs for health care, that average score was 4.23 ± 0.67 points.